KERAGAMAN GENETIKA IKAN BETUTU (Oxyleotris sp.) DARI WADUK PANGLIMA BESAR SOEDIRMAN BANJARNEGARA DAN WADUK RAWA PENING SALATIGA GENETIC DIVERSITY OF BETUTU (Oxyleotris sp.) IN PANGLIMA BESAR SOEDIRMAN DAM AT BANJARNEGARA REGENCY AND RAWA PENING BASIN AT SALATIGA CITY - Abulias, Muh. Nadjmi; Bhagawati, Dian (Pembangunan Pedesaan, 2010)
A knowledge concerning genetic diversity of betutu is vital as a basis for their conservation. This research aimed to know genetic diversity of betutu (Oxyleoris sp.) in General Soedirman Dam located in Banjarnegara Regency and Rawa Pening Basin in Salatiga City. The perceived variable was isozyme polymorphism. Horizontal starch gel electrophoresis was used to visualize isozymes band pattern. The result is expected provide data for their management and to avoid adverse effect of inbreed pressure on the next generation. The result of showed that population of betutu from Soedirman Dam could express 12 of loci and five of them were polymorphic. The population from Rawa Pening could visualize a number of 10 loci and four of them were polymorphic. These proved that betutu population from Soedirman Dam had higher genetic diversity than those from Rawa Pening Basin. This implied that the population from Soedirman Dam could be used as local genetic resources.